Analisis Interpretasi Tugu Parameswara di Bundaran Jakabaring - Palembang - Patriansah, mukhsin (UNIVERSITAS INDO GLOBAL MANDIRI)
This Parameswara monument is a sculpture artwork created to welcome PON 2004 ago. Analysis of this work will use the aesthetic approach, in addition to its monumental form of this work is also closely related to the history of Palembang as the center of the greatest kingdom civilization in the archipelago of the archipelago of Sriwijaya. As one of the great kingdom of Sriwijaya kingdom has a strong influence on the earth archipelago. This is evident until now from the traces he left behind. Likewise with the work of sculpture Parameswara is a work of sculpture symbolic abstraction created by Rita Widagdo. Rita Widagdo is one of the artists living in modren age, this is certainly very influential in the creation of this sculpture artwork. The presence of sculpture art works also provide an interpretation of the development of the times. Parameswara sculpture is not just a beautiful natural manifestation of natural simplification by simply capturing the essence of an object in the amatinya, the object is a creative stimulus so that the resulting work is an abstraction of reality. In the manifestation Rita Widagdo tends to use a concave and convex lines firmly to give the impression of a courage and strength that is the result of interpretation of Parameswara figures. Parameswara statue is a symbol of unifying Malay clumps in the archipelago. The reason, almost all Malays in the archipelago, especially in Malaysia, Singapore, southern Thailand, and Brunei originated from Palembang. They are all descendants of Parameswara and his followers, a commander of Palembang After the fall of Sriwijaya, Iskandar Shah or Parameswara fled north to find a new settlement.